Prevalência estimada e fatores associados à hipertensão arterial em indígenas Krenak do estado de Minas Gerais - Cristiane Alvarenga Chagas (2018)
Introduction: A complex scenario of illness has been observed in recent decades among Brazilian indigenous peoples. The chronic non- communicable diseases, responsible for the greatest burden of disease in the world, have also affected these people. This may be associated with changes in the way of living and interaction with other societies. The arterial hypertension previously not observed among the Indians, is now prevalent, being considered a health problem in Brazilian indigenous peoples. Objective: To analyze the factors associated with arterial hypertension in indigenous people of the Krenak villages in the State of Minas Gerais. Materials and Methods: It is a cross-sectional study carried out with natives aged> 18 years of both sexes of the Krenak indigenous land, Minas Gerais. Data on sociodemographic variables, lifestyle and eating habits were collected using a structured questionnaire. Weight and height were measured for subsequent calculation of body mass index, waist circumference, capillary glycaemia and blood pressure (BP). Participants who presented systolic BP> 140 mmHg and / or SBP> 90 mmHg and / or under the use of antihypertensive drugs, were considered with SAH. Data analysis was performed in the Stata program, version 14. A bivariate analysis was performed between the independent variables and the dependent variables, these were estimated using the Pearson chi-square test. The strength of the association was measured by the prevalence ratio using Poisson regression. A multivariate statistical model was constructed with the Poisson regression technique and adapted theoretical model. All the variables that presented P < 0.20 in the bivariate analysis were inserted in the elaboration of the final multivariate model. Results: 183 indigenous people participated in the study. The majority of participants were female (52.8%). The prevalence of hypertension was 31.1% (CI95% 24.37 37.92). After adjusting the variables, the factors associated with hypertension among the natives were: Those in the most advanced aged groups, 30-39 years (RP= 3.99 CI 95% 1.49-10.69) / 40-49 years (RP= 5.95% CI: 1.8514.08) / 50-59 years (RP = 6.23 CI 95%2.05-18,90) / 60 years or more (RP = 7.45 CI 95% 20.97) and abdominal obesity with a very high risk for cardiovascular diseases (RP = 2.83, 95%CI 2.54-9.40). Conclusion: The prevalence of hypertension between indigenous Krenak was high, which indicates the need to think about interventions for the prevention and control of arterial hypertension, since this may have irreversible consequences. Such actions must be sustainable and adequate to the resources available in the territory due to a huge sociodiversity among indigenous people.